Adverse reactions to A (H1N1) influenza vaccine in a Peruvian healthcare workers public institution - Álvarez-Falconí, Pedro P. (2011)
Introduction: In April 2009 an influenza outbreak caused by a new virus, influenza A (H1N1), started in the Mexican-American border. Later this outbreak became pandemic but not as severe as initially thought; immunization programs were developed, and vaccines used led to vaccine adverse events (VAE). Objectives: To assess a possible relationship between spontaneously reported VAE and influenza A H1N1 vaccination in an institute’s healthcare workers. Design: Prospective and descriptive study based on spontaneous notification. Setting: Instituto Nacional de Salud headquarters, Lima, Peru. Participants: Healthcare workers. Methods: Spontaneously notified VAE were recorded in specially designed sheets. An algorithm was used in order to assess a cause-effect relationship. Main outcome measures: Influenza A(H1N1) vaccination adverse events. Results: There were three spontaneous reports in 148 vaccinated healthcare workers (2%). Cause-effect relationship was deemed as ‘certain’ for cases presenting with fever and fatigue, and as ‘possible’ for cases presenting with respiratory involvement (acute pharyngitis, nasal catarrh, acute and catarrhal bronchitis). Conclusions: Among the few healthcare workers who developed VAE, respiratory involvement reported in three women and considered as having a ‘possible’ cause-effect relationship may be interpreted as women being more susceptible to this event compared to men. Fever and fatigue were considered as having ‘certain’ cause-effect relationship. The smaller number of elderly infected persons reported in this country and in others may be explained by the presence of ‘protective antibodies’ in these persons. Key words: Vaccine adverse event, influenza, pandemics, influenza A (H1N1) 2009, Peru.